Kredo Nicea dalam Konteks Indonesia: Studi Literatur Sistematis - Silalahi, Bonnarty; Tualangi, Lerry Christofal J. (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
The Nicene Creed is a foundational document in Christian theology, shaping core understandings of the Trinity and Christology. While global academic discussions on the Creed continue to evolve across historical, systematic, and ecumenical dimensions, research within the Indonesian context remains limited and lacks systematic mapping. This study employs a Systematic Literature Review (SLR) method, guided by the PRISMA and SPIDER frameworks, to analyze scholarly trends related to the Nicene Creed in Indonesia. From an initial pool of 785 articles sourced from Google Scholar, 50 met the inclusion criteria. The findings show a predominance of theological discourse (35 articles) over studies addressing practical or social implementation in church life (15 articles). This imbalance highlights a gap in contextual theological engagement and indicates a limited process of translating the Creed within local ecclesial cultures. It also points to the need for further exploration of how congregations perceive and embody the Nicene Creed in relation to their cultural and religious settings. This study contributes to the academic mapping of the Nicene Creed in Indonesia and identifies potential directions for future research. These include exploring the application of the Creed within local contexts—particularly from a postcolonial perspective—as well as conducting comparative studies with other belief systems in Indonesia within the framework of religious and cultural plurality. Such efforts would deepen the contextual relevance of the Nicene Creed and enrich theological discourse in diverse Indonesian settings.